Human Coronavirus 229E: Receptor Binding Domain and Neutralization by Soluble Receptor at 37°C - Breslin, Jamie J. (American Society for Microbiology, 2003)
Truncated human coronavirus HCoV-229E spike glycoproteins containing amino acids 407 to 547 bound to purified, soluble virus receptor, human aminopeptidase N (hAPN). Soluble hAPN neutralized the infectivity of HCoV-229E virions at 37°C, but not 4°C. Binding of hAPN may therefore trigger conformational changes in the viral spike protein at 37°C that facilitate virus entry.